The Historiography of the Left in Chile: A Burgeoning Field; [la Historiografía Sobre Las Izquierdas en Chile: Un Campo en Expansión] - Alvarez-Vallejos, R (Centro de Estudios Historicos de los Trabajadores y las Izquierdas, 2019)
The following article examines the development of the historiography of the Left in Chile, from the transition to democracy in 1990 to the present. It argues that the field has experienced a significant expansion and diversification, propelled by social and political changes within Chile and by changes in the faculty of the country’s main universities. It analyzes, first, the pioneering trends and the work of those who, inspired by the political and academic debates of the 1980s, led the scholarship in new directions. It provides, then, a panoramic view of the scholarship on the Chilean Left in the last three decades. © 2019, Centro de Estudios Historicos de los Trabajadores y las Izquierdas. All rights reserved.